New Syphilis Cases in Older Adults, 2004–2019: An Analysis of Surveillance Data From South China - Cheng Wang (Frontiers Media S.A., 2021)
Background: Sexual health among older adults is a major public health concern globally. The syphilis burden is increasing in older adults in China. This study aimed to describe factors associated with syphilis infection and diagnosis among older adults in China during a 16 year period.Methods: Using 16 years of data (2004–2019) from the syphilis case report system of Guangdong, China, we compared data from older adults (aged ≥50 years) with those from younger people (aged 15–49 years). We compared the two age group with the Chi-square test for difference, and Joinpoint regression models to assess the temporal trends.Results: During the study period, 242,115 new syphilis diagnoses were reported in older adults. The mean notification rate of new diagnoses was 64.1 per 100,000 population across the entire 16-year period, which significantly increased over time (average annual percent change [AAPC] 16.2%, 95% CI 13.7–18.7). Syphilis diagnoses increased significantly over time among less developed cities and older women. In 2019, compared with younger adults, newly diagnosed older adults were more likely to be male, native to reporting city, had unknown transmission routes, and were diagnosed late.Conclusion: Our findings call for an urgent need to deliver more targeted prevention interventions for older adults, such as strengthen awareness among health care providers, and integration of syphilis services and primary health care for older adults.